“ANY IDEA FOR A WARM-UP?”, WHEN REQUESTS FOR HELP LEAD TO TEACHER PROFESSIONAL DEVELOPMENT - Kirsch, William (Revista X, 2019)
This paper discusses teacher-room interaction in a community of practice (WENGER, 1998) of student teachers of English as an Additional Language, focusing on the dyad requests for help—offers of help, which often take place in the community. The community was affiliated with extinct Languages without Borders in a large university in south of Brazil. The research is affiliated with the paradigm of practice theory (YOUNG, 2009) and uses qualitative and interpretive methodology (ERICKSON, 1990; Mason, 2002). It is possible to conclude that the kind of teacher-room interaction presented in this paper greatly contribute to student teachers’ professional development throughout their trajectory in the community.